2021
DOI: 10.1021/acsinfecdis.0c00839
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Gynecological Cancers: A Summary of Pathogenetic Mechanisms and Future Directions

Abstract: Over the past 20 years, important relationships between the microbiota and human health have emerged. A link between alterations of microbiota composition (dysbiosis) and cancer development has been recently demonstrated. In particular, the composition and the oncogenic role of intestinal bacterial flora has been extensively investigated in preclinical and clinical studies focusing on gastrointestinal tumors. Overall, the development of gastrointestinal tumors is favored by dysbiosis as it leads to depletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 261 publications
0
46
0
Order By: Relevance
“…In fact, any imbalance in the gut microbiome can cause corresponding physiological effects. Previous studies have shown that imbalances in the gut microbiota could lead to an increase in estrogen secretion (Plottel and Blaser, 2011), which was associated with endometriosis, endometrial cancer, and other uterine diseases (Borella et al, 2021). However, its role in endometritis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, any imbalance in the gut microbiome can cause corresponding physiological effects. Previous studies have shown that imbalances in the gut microbiota could lead to an increase in estrogen secretion (Plottel and Blaser, 2011), which was associated with endometriosis, endometrial cancer, and other uterine diseases (Borella et al, 2021). However, its role in endometritis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the microbiome associated to cancerogenesis were also observed for prostate carcinoma and breast cancer [32,33] and could explain our findings as increased incidence of prostate cancer or breast cancer appears to be associated with IBS. Furthermore, chronic inflammation and activation of the immune system may promote extraintestinal tumorigenesis, e.g., gynecological tumors like endometrial, cervical or ovarian cancer [34]. At least in a subgroup of IBS patients, an increased cytokine release was found to be connected to a low-grade inflammatory reaction [7].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, an abundance of Clostridiales in gut microbiome correlated to patients who respond positively to PD-1 blockade therapy, while the nonresponders’ microbiomes were enriched with Bacteroidale [ 76 ]. In addition, the previously mentioned studies have demonstrated that there are three species ( Bifidobacterium , Akkermansia muciniphila , and Faecalibacterium ) that could be considered to be immune adjuvants in PD-1/PD-L1 immunotherapy.…”
Section: Modulation Of Antitumoural Therapies Efficacy and Toxicity By Gut Microbiotamentioning
confidence: 99%